1992
DOI: 10.1002/ajp.1350260106
|View full text |Cite
|
Sign up to set email alerts
|

The costs of infant carrying in captive cotton‐top tamarins

Abstract: Marmosets and tamarins have a communal rearing system in which all group members help to care for the twin infants characteristic of this family of primates. Helpers are likely to incur time and energy costs by contributing to infant care. Predictions that cotton-top tamarin (Saguinus oedipus) helpers would change their behavior when carrying infants because of reduced mobility and/or a need for increased vigilance were tested in a captive colony. Tamarins carrying an infant spent significantly less time feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 20 publications
3
48
2
Order By: Relevance
“…In Study 1, female marmosets faced with the impending demands of nursing and carrying newly conceived litters during early infant care significantly reduced their investment in their current litters-perhaps shifting investment away from their current litters to ensure sufficient resources for upcoming litters. Although studies have indicated that callitrichid caregivers sometimes reduce the energetic burden of infant care by spending less time foraging and traveling while transporting infants (e.g., saddle-back tamarins: Goldizen, 1987; cotton-top tamarins: Price, 1992c; see review in Tardif, 1994), and that some may be physically limited in their ability to travel while carrying infants (common marmosets: Schradin and Anzenberger, 2001), our results are consistent with recent reports that energetically challenged callitrichid females may actually provide less care to their offspring than females that are in better condition and/or have access to higher quality resources. Tardif et al (2001) reported that, among common marmosets, smaller females engaged in fewer nursing bouts than larger females, and Bales et al (2002) found that females with the lowest body weights also exhibited the lowest levels of carrying effort.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Study 1, female marmosets faced with the impending demands of nursing and carrying newly conceived litters during early infant care significantly reduced their investment in their current litters-perhaps shifting investment away from their current litters to ensure sufficient resources for upcoming litters. Although studies have indicated that callitrichid caregivers sometimes reduce the energetic burden of infant care by spending less time foraging and traveling while transporting infants (e.g., saddle-back tamarins: Goldizen, 1987; cotton-top tamarins: Price, 1992c; see review in Tardif, 1994), and that some may be physically limited in their ability to travel while carrying infants (common marmosets: Schradin and Anzenberger, 2001), our results are consistent with recent reports that energetically challenged callitrichid females may actually provide less care to their offspring than females that are in better condition and/or have access to higher quality resources. Tardif et al (2001) reported that, among common marmosets, smaller females engaged in fewer nursing bouts than larger females, and Bales et al (2002) found that females with the lowest body weights also exhibited the lowest levels of carrying effort.…”
Section: Discussionmentioning
confidence: 99%
“…Carrying callitrichid infants comes at a 21% increase in the caloric cost (per minute) of traveling (Tardif, 1996). Infant transport is also associated with other costs, such as decreased foraging and feeding time (e.g., saddle-back tamarins: Goldizen, 1987;cotton-top tamarins: Price, 1992c; also see review in Tardif, 1994) and increased risk of predation (cotton-top tamarins: Price, 1992c; see review in Tardif, 1994). Conception APCID was operationally defined as conception four weeks following birth, and later, as maternal caregiving effort is not expected to be as intensive during this time period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mothers were determined to be carrying infants when one or more infants were observed clinging to the body or pelage of a parent or alloparent. We did not distinguish between the carrying of one versus two infants, because infants born into large social groups are not generally carried by the same individual (cotton-top tamarin: Price, 1990Price, , 1992a, and there is evidence that there are few additional costs associated with carrying more than one infant at a time (e.g., saddle-back tamarin: Goldizen, 1987; cotton-top tamarin: Price, 1992b).…”
Section: Behavioral Measuresmentioning
confidence: 99%